Microscopic Characteristics of Fault Gouge in Minor-Surface-Rupture Faults: A Case Study in the Longmenshan Fault Zone, Eastern Tibetan - Li, Yanbao; Chen, Lichun; Ran, Yongkang; Chang, Yuqiao (Frontiers in Earth Science, 2022)
Active faults with potential earthquake magnitude of 6-7 are often incorrectly identified as non-Holocene active faults by traditional geological methods due to their co-seismic displacements were very small or even did not reach to surface, and are defined as minor-surface-rupture faults. Geological studies associated to the 2013 Lushan Ms 7.0 earthquake show that the Dachuan-Shuangshi fault (DSF) in the southern segment of Longmenshan fault zone (LFZ) is a minor-surface-rupture fault. This study focuses on the microstructure and mineral composition of the fault gouge in the DSF, using the methods of optical microscopy, scanning electron microscope (SEM) and X-ray diffraction (XRD); then, contrasts our results with the previous achievements in Beichuan-Yingxiu fault (BYF), one major of seismogenic faults of the 2008 event, in the middle-northern segment of the LFZ. The results show that the microscopic characteristics of fault gouge of DSF are obviously different from those of BYF in the following aspects: 1) The thickness of fault gouge produced by one fault event is less than 5 mm; 2) Under microscope, no obvious micro-crack was examined in surrounding rock around fault gouge, and discontinuous micro-cracks and untypical S-C fabrics in fault gouge were observed; 3) Under SEM, reworked fragments was rare in the fault gouge; 4) XRD mineral analysis reveal that the total clay content is less than 50%, the content of Kaolinite is obviously higher than that of Clinochlore, and the content of Illite/Smectite mixed layer is less than 30%. Contrastive analysis reveals the differences, between the microscopic features of fault gouge of the DSF and the BYF, are systematically. Therefore, the above microscopic characteristics identified from the fault gouge in the DSF may be used as auxiliary indicators to identify minor-surface-rupture faults, and make up for the limitations of traditional geological methods.